Korean Grammar: The Complete Guide to Speaking Korean Naturally - Kim, Soohee (Routledge Advances in Korean Studies, 2017)
Each chapter provides clear grammatical explanations with charts and examples for each construction, showing how it is used in various contexts. All Korean words and sentences are given in both Korean Hangul script and Romanized form, with English translations to assist beginning learners. Fundamental concepts like honorifics, formal and informal speech styles, verb endings and complex sentence constructions are all presented in simple and clear terms to make these constructions accessible to learners at every level. Exercises at the end of each chapter reinforce the learning process.